Nasolabial Cyst - Caner Sahin (Case Reports in Medicine)
Nasolabial cyst is a rare nonodontogenics, soft-tissue cyst occurring in the sublabial area and anterior maxillary region. The patient usually presents with a slowly enlarging asymptomatic swelling. They are usually diagnosed in early stages because of cosmetic problems. In our paper we report a nasolabial cyst of a 53-year-old man and discuss the diagnosis, differential diagnosis, and treatment in the light of the literature.